Soliton mode-locking in thulium-doped fibre laser by evanescent field interaction with reduced graphene oxide-titanium dioxide saturable absorber. (11th June 2019) - Ahmad, H; Ramli, R; Monajemi, H; Reduan, S A; Yusoff, N; Ismail, M F
Abstract: Soliton mode locking pulse generation in a thulium-doped fibre laser (TDFL) by evanescent wave interaction from a D-shaped fiber coated with rGO-TiO2 nanoparticles is proposed and demonstrated. The rGO-TiO2 nanoparticle coating serves as a saturable absorber (SA), and generates a mode locked pulse with a repetition rate, average output power and pulse width of 9.28 MHz, 11.17 nW and 1.49 ps respectively. The proposed laser has a central lasing wavelength of 1939.4 nm, which is the longest as of yet generated by evanescent wave interaction in a TDFL. An average signal-to-noise ratio of around 50 dB is obtained from the generation pulse, with minimal power and wavelength fluctuations indicating high stability. The proposed laser would have significant applications in various fields, particularly medicine for its operation in the eye-safe region of 2 µ m.